Community Development, Local Wisdoms, and Ineffective Government Aid: The Case of Lombok Post-Disaster House Reconstruction Project - Mira Ardhya Paramastri (Institute of International Studies, 2020)
Despite the high frequency of disasters, post-disaster development projects in Indonesia have yet been implemented effectively. Such may not be easily reflected through the number of aid projects given, for the reality is much more complex. This article believes that the significance of development projects should be assessed from the aid recipients' perspective. The excess rebuilding back in Aceh's 2004 post-disaster case is one example that shows the importance of paying attention to recipient needs from their perspective rather than aid giver perceptions. The post-disaster condition in Lombok back in 2018 could serve as an example to show the effectiveness of post-disaster development in Indonesia recently. In accordance, this article aims to show how the post-disaster community development programs implemented by multi-stakeholders in Indonesia, especially government-initiated ones, have yet successfully fulfilled Lombok post-disaster victims' needs. The article also found that active initiation from the locals and careful attention to local potentials and wisdom is crucial to determine post-disaster development's success. Such a conclusion is based on the assessment of whether the programs have fulfilled community development principles, in addition to satisfying the victim's human security.